The Future of Islamic Education in Europe: Challenges, Opportunities, and Emerging Paradigms - Ahmad Nabriz; Ahmad Faizal Syahrul Azmi; Abubaker Kashada; Rahmat Ullah; Ajoy Chandra (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
The future of Islamic education in Europe is increasingly shaped by demographic transformation, cultural diversity, digitalization, globalization, and evolving educational expectations. This study aims to examine the major challenges, opportunities, and emerging paradigms influencing the development of Islamic education across contemporary European societies. The research employs a qualitative library research approach through a systematic review and thematic analysis of scholarly literature including peer-reviewed journal articles, academic books, policy documents, and international reports. The findings reveal that Islamic education is undergoing a significant transition from identity-preservation models toward more integrative approaches emphasizing citizenship education, intercultural competence, digital literacy, ethical development, sustainability, and human centered learning. The study further identifies digital transformation, artificial intelligence, curriculum innovation, teacher professionalization, and social cohesion as key factors shaping future educational development. The novelty of the research lies in the development of the European Islamic Education Transformation Framework (EIETF), which synthesizes Islamic educational philosophy, citizenship education, intercultural learning, digital pedagogy, artificial intelligence, and human-centered education into a comprehensive model for educational transformation. The study concludes that Islamic education possesses substantial intellectual, ethical, and pedagogical resources for contributing to inclusive, democratic, and technologically advanced European societies while preserving its distinctive educational identity